Predictors of Failure Following Fixation of Trochanteric Fractures - Abdennadher, Achraf; Hjaiej, Safa; Ayari, Rabie; Mallat, Youssef; Triki, Ramy; Amri, Khalil (Open Access Macedonian Journal of Medical Sciences, 2023)
BACKGROUND: Trochanteric fractures are frequent and mainly affect the elderly causing autonomy loss. Their incidence is increasing, and they are associated with substantial morbidity and high cost. AIM: The aim of our study was to identify epidemiological, radiological, and technical predictors of failure of trochanteric fracture fixation in the elderly. METHODS: We conducted a retrospective study including 188 patients aged over 65 years, who underwent surgery for trochanteric fractures, in the period between 2015 and 2020 at the orthopedics department of the Military Hospital of Tunis. The minimum follow-up was 12 months. RESULTS: Thirty-four patients had a mechanical failure (18.1% of cases), including 12 cases of cephalic screw migration (CSM) (6.4%), 12 cases of disassembly (6.4%), eight cases of malunion (4.3%), and four cases of non-union (2.1%). Bone fragility with a Singh index ≤III was associated with CSM, disassembly of fixation material, and malunion (respectively, p < 0.001; p = 0.01 and p = 0.044). Reduction quality was associated with disassembly (p < 0.001) and CSM (p = 0.004). Eccentric screw positioning on anteroposterior (p < 0.001) and lateral views (p = 0.018), high tip-apex distance (TAD) (p < 0.001), and calcar-referenced TAD (p < 0.001) were predictive of CSM. Logistic regression analysis showed that poor reduction quality was an independent factor associated with the occurrence of mechanical complications. Functional outcomes were assessed using Parker and Postel Merle d’Aubigné scores. CONCLUSION: To minimize the risk of mechanical complications, the surgeon must pay close attention to the fracture reduction and to the correct positioning of the cervical screw.